Cooperation or fall behind? The influence of goal structure on two-person decision making under uncertainty and risky contexts - Can Zhang; Sihua Xu (Humanities & Social Sciences Communications)
Abstract Goal structures are fundamental to social interactions, shaping the dynamics of cooperation and competition. However, how these structures influence the performance of dyadic decision-making, particularly under conditions of uncertainty and risk, is not yet fully understood. This study employed three sub-studies to investigate how goal structures influence task performance in dyadic decision-making and to explore the boundary conditions of these effects. Study 1 utilized the Balloon Analogue Risk Task (BART) to assess choice preferences under uncertainty, comparing scenarios with and without a shared goal. The results indicated that individuals performing under a shared goal outperformed those with an individual goal. Study 2 applied the Iowa Gambling Task (IGT) to investigate decision-making responses in competitive and cooperative goal structures. Participants showed a tendency toward risk avoidance in the risky phase compared with the ambiguous phase under cooperation, a pattern not observed under competition. Study 3 also used BART to explore how social value orientation (SVO), SVO-type homogeneity within dyads, and dynamic shifts in goal structures influenced task performance. Findings revealed that prosocial dyads scored higher on BART in cooperative conditions compared to competitive ones, with SVO-type homogeneity and shifts in goal structure moderating these effects. Collectively, our research suggests that goal structures significantly influence two-person decision-making, shaping decision-making tendencies and task performance in complex settings.